Cradle-to-gate life cycle assessment of self-compacting concrete incorporating alternative materials: a case study - Zanellato Coelho, Felipe; Zulcão, Robson; Calmon, João Luiz; Vieira, Darli Rodrigues (Revista Principia, 2020)
Many studies have described the successful incorporation of wastes and industrial byproducts, here called alternative materials (AMs), into self-compacting-concrete (SCC) mixtures from a technical point of view. Such studies usually considered a universal truth that incorporating these materials into the concrete matrix helps improve their eco-efficiency. Therefore, the objective of this study is to associate SCC production that incorporates AM with the life cycle assessment (LCA) methodology to compare mixtures in a specific United States scenario. SimaPro software, the IMPACT 2002+ impact assessment method, the Ecoinvent database and a 1 m3 functional unit with the cradle-to-gate system boundary were used. An analysis of total impact, global warming, impact intensity and most impactful processes was performed. According to the criteria analyzed, the mixtures with the best environmental gains are characterized by the partial or total replacement of cement by AMs classified as supplementary cementing materials (SCMs). Other cases did not yield significant environmental gains, such as the use of concrete and glass waste as aggregates, serving only as an alternative to their final disposal. In addition, when there was excessive energy consumption for waste recycling, such as for rubber and polyethylene terephthalate (PET) recycling, the environmental efficiency of the SCC deteriorated.